Galectin-10 Characterization in Cleft Lip Palate – Affected Palatal Tissue - Rone, Alise Elizabete; Pilmane, Mara (Acta medica Lituanica, 2025)
Background. Cleft lip palate is one of the most common craniofacial birth defects in humans. Multiple defense factors have been described to have possible involvement in the failure in palatal shelve elevation, migration and fusion, most importantly, the role of chronic inflammation. A widespread presence of Gal-10 in different local inflammatory processes has been discussed before, however, knowledge of its involvement in local tissue inflammation in the postnatal cleft palate and tissue regeneration is scant. This study focuses on the detection of appearance and a possible role of Gal-10 in the cleft-affected facial tissue regarding its ontogenetical aspect.Materials and Methods. Craniofacial cleft tissue material was obtained from 21 children aged 8 months to 12.7 years undergoing veloplastic or uranoplastic procedure with non-syndromic craniofacial cleft diagnosis in milk or mixed dentition. Control groups for milk dentition were 5 subjects without orofacial defects for milk dentition and 3 subjects with plastic of superior lip frenula for mixed dentition. The number of factor positive cells in the control group and the patient group tissue was evaluated by using the semiquantitative counting method. The data were evaluated with the use of nonparametric statistical methods.Results. Elevated levels of Gal-10 were found in the epithelium in correlation with age, from milk to mixed dentition, as well as in both the control and the patient samples. Notable differences in expression can be seen by comparing the milk and the mixed dentition patient muscle tissue, where the milk dentition palate shows a more elevated factor expressed in comparison to the mixed dentition palate.Conclusions. The nearly total absence of Gal-10 in the healthy palate with an increase of its expression in the palatal epithelium from the milk to mixed dentition age of cleft-affected children suggests the possible role of this factor in providing the local defense function and the epithelium barrier function. The palatal muscles are not the main place for Gal-10 expression either in healthy or in cleft condition-affected individuals. The sporadic and insignificant appearance of Gal-10 only in the healthy milk dentition age and the mixed dentition age cleft-affected palatal connective tissue prove individual changes in the palatal tissue which does not depend on the specific disease.
Keywords: galectin-10; cleft lip; cleft palate